I'm fine with Immigrants, but ...: Attitudes, ethnic diversity, and redistribution preference - Mustafa Coban (Julius Maximilian University of Würzburg, Chair of Economic Order and Social Policy, 2017)
Combining the link between ethnic heterogeneity, attitudes towards immigrants, and the support of redistribution, predictions are made about natives' preference for redistribution depending on interethnic contact, perceived outgroup threats, and natives' social distance from immigrants. The econometric specification explicitly considers the simultaneous effects of ethnic heterogeneity on attitudes towards immigrants and those attitudes on the redistribution preference. Applying bivariate recursive probit estimations enables the decomposition of marginal effects into a direct and an indirect effect. The empirical assessment, based on a cross-section of 18 European countries from 2014, shows that natives' perceived outgroup threats directly decrease their preference for redistribution, whereas interethnic contact indirectly increases their redistribution preference through less anti-immigrant attitudes. If immigrants are perceived as a threat to the culture or social life in a country, a native's probability of supporting more governmental redistribution decreases by 6.4 percent or 8.2 percent, respectively. However, if ethnic heterogeneity rises, this probability increases by 0.8 percent. In contrast, there is no significant association between natives' social distance from immigrants and their preference for redistribution. These results are robust to IV estimation strategies which control for the possibility of natives' selective out-migration and reverse causality. Taking the natives' and immigrants' average incomes into account, the ethnic income gap between natives and immigrants strengthens the negative impact of perceived outgroup threats if immigrants earn much less than natives in a country.
Keywords: C30; D31; D63; D72; F22; H20; 330; preference for redistribution; immigration; ethnic diversity; attitudes towards immigrants; bivariate recursive probit